Analisis Dukungan Keluarga dengan Tingkat Kecemasan pada Pasien Pre Operasi di RS Pertamedika Ummi Rosnati Banda Aceh - Syukran Rahmatillah; Urip Pratama; Muhammad Daud (Jurnal Sains dan Kesehatan, 2024)
Until now, most people think that surgery is a scary experience. There are many problems that may occur during the operation process or after the operation, this can trigger fear in the patient where the patient is afraid that the operation they are undergoing will fail or even result in death. The aim of the research was to determine the relationship between family support and anxiety levels in pre-operative patients at Pertamedika Ummi Rosnati Hospital, Banda Aceh. This research method uses an analytical design with a cross sectional approach with a sample size of 93 preoperative patients, the sampling technique is Consecutive Sampling, univariate and bivariate analysis using the chi square test. The results of the study showed that the majority experienced anxiety in the severe category, 38 respondents (40.9%) and the majority of family support was in the moderate category, 51 respondents (54.8%), with p value = 0.024. The conclusion is that there is a relationship between family support and anxiety in preoperative patients. It is hoped that the research site will improve health services, especially for pre-operative patients, by providing support and motivation so that patients do not experience excessive anxiety.